‘Clearing the air’: Common drivers of climate-smart smallholder food production in Eastern and Southern Africa - Branca, G.; Perelli, Chiara (Elsevier, 2020)
African smallholders should adopt climate-smart agriculture to make a sustainable transition towards cleaner, circular and more productive food systems. Farmers must play a key role in that process. However, the adoption and diffusion of climate-smart technologies have been slow. Here, a cross-sectional econometric analysis using primary data on sustainable farming practices in the cereal-legume farming systems of Ethiopia, Malawi, South Africa and Tanzania is applied to analyse the drivers and intensity of innovation adoption. Socio-economic barriers reduce adoption intensity among marginalised farmers, and proper incentives are needed to overcome them. Business links between technology-ready smallholders and small-to-medium enterprises must be created to enable the uptake and scaling-up of innovations and the development of industrial application models. Such results can support the design of evidence-based strategies for the sustainable transformation of production systems. While national climate policies already include climate-smart agriculture as an adaptation blueprint, policy makers need empirical evidence to support large-scale adoption. This research is an innovative contribution to that effort. It uses a unique household dataset where data is scarce; it considers the impact of smallholders’ conditioning factors on technology climate-smartness level; and it estimates the correlations among a wide range of practices, agro-ecologies and geographical contexts.